PERANAN NOTARIS DALAM PENDIDIKAN HUKUM BAGI MASYARAKAT - Budi, Muhammad Afet (Jurnal Advokasi, 2016)
The society who lived in the country organized by rule of law (rechtstaat) is should have known about the laws that regulate their daily life. In general fact, there are so many people in Indonesia, asspesialy in West Nusa Tenggara, who have less knowledge or understanding about the law. It makes they cannot complete their legal issues by themselves, such as the using of the third partyâs service in the registration of land ownership rights. Moreover, not all of the society has the same opportunity and ability to have an education about the law and they should be given comprehensive understanding about it. In order to optimize the potential skill, the notary public offered to educate and give more comprehensive understanding about the law to the society.The study revealed that a notary public did not have any legal responsibility to actively participate to increase the law understanding of the society. However, considering the potential skill about the law that a notary has, morally they have to take a role in increasing societyâs understanding about the law.